Homeopathy in Malaysia / Mohamad Arif Aizuddin Mohd Ramli...[et.al] - Mohd Ramli, Mohamad Arif Aizuddin; Abd Rashid, Muhammad Danial; Mohamad Hood, Hanisah Nurizzati; Ariff Hisham, Muhamad Imran (Faculty of Communication & Media Studies, 2018)
Advancement of technologies throughout the year have produce different kind of medicine. Despite that people seeks homeopathy as source of medication, especially in Malaysia. Debate for the best form of medicine has been going around between homeopathy and conventional medicine. This study is conduct to identify the level of awareness between the effectiveness of homeopathy and modern medicine. The study indicated that the public are more aware that effectiveness of modern medicine is more high (M= 3.309) and homeopathy were (M= 2.81).